Omni-Channel Marketing Strategy: Measuring the Effect of Channel Integration and Customer Data Utilization on Customer Satisfaction through Customer Experience. - Andika Prasetya Nugraha; Adnan Adnan; Dewi Permata Sari; Rosita Septiani; Adesarmini Adesarmini (International Journal of Economics, Business and Innovation Research, 2024)
The study explored the impact of channel integration and customer data utilization on customer satisfaction in an omni-channel marketing strategy. Using a simple random sampling method with 98 respondents from a variety of demographics, the results of the analysis showed that channel integrations and client data exploitation have a complex influence on customer experience and satisfaction. Although channel integrating and user exploitation of customer data are important, they are not statistically significant for customer satisfactions. Other factors like product quality, personalization, and direct interaction were more influential. Consistent, comfortable, responsive, and satisfying customer experiences have proven to enhance loyalty and satisfaction. The research highlights the importance of periodic customer satisfaction evaluation to identify areas of improvement and adjust strategies to improve overall satisfaction. These findings make a significant contribution to the development of the theory and practical applications for optimal omni-channel strategies.